The Conceptual Analysis of Integrating Interactive Digital Media in Islamic History Education: The Potential of Using Canva - Dian Annisa; Azizatur Rosyidah; Abdul Bashith (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
This study aims to conceptually analyze the integration of interactive digital media in Islamic Cultural History (SKI) learning, focusing on the use of Canva as an innovative learning medium. The background of this study stems from the low interest and participation of students due to the dominance of conventional methods that are less interactive, as well as the lack of research on how digital media such as Canva can be effectively integrated into Islamic-based learning. Using a qualitative approach through conceptual literature review, this study analyzes various scientific sources from academic databases (Google Scholar, DOAJ, ScienceDirect) with inclusion criteria of pedagogical relevance and exclusion of non-educational technical publications, then analyzed thematically to identify conceptual patterns and pedagogical implications. The results show that Canva has great potential to improve the effectiveness of SKI learning through concept visualization, digital project collaboration, and spiritual value integration, while also developing 21st-century skills such as critical thinking and creativity. The implications are that teachers need to improve their digital literacy and innovative pedagogy, the curriculum needs to accommodate value-based interactive media, and policymakers need to strengthen infrastructure support and educational technology training. However, this study is limited to conceptual analysis without empirical data, so further studies are recommended to quantitatively and qualitatively test the effectiveness of using Canva on learning motivation, conceptual understanding, and internalization of Islamic values.